Applications of Circular Economy and Wine Tourism in Viniculture: A Case Study - Yıldız, Özay Emre (International Journal of Contemporary Economics and Administrative Sciences, 2024)
Sustainability of wine production is a major factor for its competitiveness and marketability. Traditional viniculture is more sustainable and provides solutions to modern issues. One such deduction is circular economy, encouraging resource efficiency, waste extraction, reducing costs, minimising waste and pollution. Wine tourism may also contribute in synergy, by reducing distribution costs, offering a direct sales channel, and effectively communicating the story and meaning of wine, the winemaker and the region. This paper explores the applications of these two in viniculture. A case study has been conducted on a small-scale winemaker in Urla, Izmir, comprising of interviews and participant observation. The findings exhibit real-life, synergistic examples. Applications of circular economy in small-scale viniculture are shown to increase resource efficiency, close production loops, limit waste & pollution and add value to the product. Wine tourism, while reducing costs and increasing sales, was reported to be an efficient direct communications channel with the visitor, granting a personality to wine. Due to its absolute advantages of enriching the product and the consumer and service provision, wine tourism closes the ultimate production loop. Synergistically, these tools may improve the profitability, marketability and the sustainability of viniculture.